The Roles of Impurities and Surface Area on Thermal Stability and Oxidation Resistance of BN Nanoplatelets - Kostoglou, Nikolaos; Stock, Sebastian; Solomi, Angelos; Holzapfel, Damian M; Hinder, Steven J.; Baker, Mark A.; Constantinides, Georgios; Ryzhkov, Vladislav; Maletaskic, Jelena; Matovic, Branko; Schneider, Jochen M; Rebholz, Claus; et al. (My University, 2024)
This study considers the influence of purity and surface area on the thermal and oxidation properties of hexagonal boron nitride (h-BN) nanoplatelets, which represent crucial factors in high-temperature oxidizing environments. Three h-BN nanoplatelet-based materials, synthesized with different purity levels and surface areas (~3, ~56, and ~140 m2/g), were compared, including a commercial BN reference. All materials were systematically analyzed by various characterization techniques, including gas pycnometry, scanning electron microscopy, X-ray diffraction, Fourier-transform infrared radiation, X-ray photoelectron spectroscopy, gas sorption analysis, and thermal gravimetric analysis coupled with differential scanning calorimetry. Results indicated that the thermal stability and oxidation resistance of the synthesized materials were improved by up to ~13.5% (or by 120 °C) with an increase in purity. Furthermore, the reference material with its high purity and low surface area (~4 m2/g) showed superior performance, which was attributed to the minimized reactive sites for oxygen diffusion due to lower surface area availability and fewer possible defects, highlighting the critical roles of both sample purity and accessible surface area in h-BN thermo-oxidative stability. These findings highlight the importance of focusing on purity and surface area control in developing BN-based nanomaterials, offering a path to enhance their performance in extreme thermal and oxidative conditions.
Keywords: thermal stability; hexagonal boron nitride; nanomaterials; nanoplatelets; nanostructures; oxidation resistance; purity; surface area